Biological Control Agent of Spodoptera frugiperda Using Bacillus thuringiensis Bacteria - Indriyani, Indriyani; Handayani, Kusuma; Firmansyah, Alvian; Pratami, Gina Dania (Al-Hayat: Journal of Biology and Applied Biology, 2025)
The main obstacle in the development of food crop production and horticulture is the attack of S. frugiperda larvae. Pest control using chemical insecticides has a long-term negative impact. The biological control of Spodoptera frugiperda larvae is accomplished by utilizing B. thuringiensis bacteria. This study aims to determine the best B. thuringiensis isolate for killing S. frugiperda larvae, to identify the most effective concentration of B. thuringiensis suspension, and to ascertain the mortality rate of S. frugiperda larvae. The design of this study was a randomized block design (RBD) with two factors. The first factor was the type of B. thuringiensis isolate, consisting of four isolates. Larval mortality data were analyzed using Analysis of Variance (ANOVA) and further tested with the Duncan test. The results obtained showed the highest average mortality of S. frugiperda larvae using isolates Bt3BP14 and Bt4TSR6. These two isolates had the highest average mortality on the third day. Bt3BP14 and Bt4TSR6 isolates have high potential in controlling S. frugiperda larvae, with an average mortality proportion of 86,67% and 66,67% observed over three days. The best doses of B. thuringiensis suspension for killing S. frugiperda larvae were 15 ml and 20 ml. It can be concluded that B. thuringiensis isolates can be used as natural biological control agents against S. frugiperda larvae that attack food crops and horticulture.